POPULISM AS A DISCOURSE OF HUNGARIAN ELITES - A. Bozóki (Сравнительная политика, 2015)
Since the end of the 19th century populist movements emerged as significant actors of the Hungarian politics. The attempts to assess populism appeared to be as ambiguous, as the attempts by politicians and pundits to describe it. The study of its development demonstrates that it is not linked to the traditional division between left and right, but represents dissatisfaction with the established elites in the society. The article considers changing nature of Hungarian populism on different stages of national history. Specific attention is devoted to the content and value of populist policies in the current Hungary.